Balancing Economic, Environmental, and Technological Systems for Sustainable Agricultural Development in Romania - Cristian BUZOIANU, Ovidiu Andrei; IACOB , Oana; Mihai MATEESCU, Vicentiu; BURLACU, Sorin (European Journal of Sustainable Development, 2024)
The aim of this research is to ascertain and evaluate the optimal equilibrium in the interaction of four critical systems: social, economic, technological and environmental. This will enable a functional process that is both dynamic and adaptable within the context of long-term sustainable development. The research centers on significant enduring obstacles, such as the expansion of the global population, strain on natural resources, and global warming, which establish a fresh framework for necessary measures to attain this equilibrium. The research methodology employed in this study encompasses an extensive examination of existing literature, along with the analysis of case studies and statistical data. The objective is to evaluate the influence of demographic and environmental factors on agriculture and rural regions. The analysis centers on the following factors: worldwide population growth, urbanization, escalating energy and fertilizer costs, strain on water resources, and the heightened susceptibility of crops and livestock to climate change. The study also analyzes the European Union’s policies and strategies designed to address these challenges by promoting food security, sustainable resource management, and equitable territorial development. The primary conclusions of the study suggest that while there is a persistent rise in the worldwide demand for food, the availability of food is constrained by various crucial factors. The factors encompassed in this context comprise of accelerated urbanization, escalating energy and fertilizer expenses, heightened strain on water resources, and augmented susceptibility of agriculture to climate change. Europe faces amplified challenges due to its aging population, impacting both the availability of agricultural workforce and the need for food. This research contributes to the comprehension of the necessity for an all-encompassing and enduring approach in agricultural and rural development policy. The study emphasizes the intricate relationship among economic, environmental, human, and technological factors. It underscores the significance of a cohesive and flexible strategy to address long-term challenges and maintain a sustainable equilibrium between economic growth, environmental preservation, and human welfare. Keywords: agriculture, sustainable development, production, Romania